2018
DOI: 10.18502/keg.v3i5.2664
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Technologies for Extraction of Platinum Group Metals from Poor Raw Materials

Abstract: .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Recently, Nekouei et al reported a review of value-added products from waste printed circuit boards. Their recommendation was on the valorisation of all materials in e-waste, including polymers, metals, and ceramics [127]. [126].…”
Section: Conversion Of Waste Metals Directly To Nanomaterialsmentioning
confidence: 99%
“…Recently, Nekouei et al reported a review of value-added products from waste printed circuit boards. Their recommendation was on the valorisation of all materials in e-waste, including polymers, metals, and ceramics [127]. [126].…”
Section: Conversion Of Waste Metals Directly To Nanomaterialsmentioning
confidence: 99%